TANTANGAN KEPEMIMPINAN PEREMPUAN DI TINGKAT LOKAL - Maria Ulfah Anshor (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Woman leadership normatively has strong legitimating basis, from theological, philosophical, or law’s perspective. However,in reality still face many obstacles, internal or external. Main agenda to struggle is around education, economic, health, and stopping violenceto woman. Several strategies for future election are: fist, review to all entire law products that contradict with gender equality principle.Second, is enhancing political education through independent civil society organizations. Third, woman participation in general election mustbe more critics to vote leader that have perspective and concern to people. Fourth, is preparing leader cadre that ready to fill 30% womanquota in legislative or executive institution on all level